Identifying patterns of alumni commitment in key strategic relationship programmes - Pedro, Ilda; Mendes, Júlio da Costa; Pereira, Luis Nobre (ICAReAlumni Conference Proceedings, 2022)
Presentation whose subject objectives are: Objective 1. To characterize the alumni commitment. Objective 2. To describe overall patterns in alumni commitment.